Degree of Contribution of Training Patterns at the Specialized Institute for Professional Training of Teachers in the Professional Development of Public School Teachers in the Sultanate of Oman - Al-Ghailani, Badria Saleh Salem; Al-Dhuhli, Rabie Amurr Ali (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree of contribution of training patterns at the specialized institute for professional training of teachers in the professional development of public school teachers in the Sultanate of Oman, to achieve the study objectives researcher used the descriptive approach. A questionnaire was designed of (46) statements, divided into two scales. After checking the validity and reliability the questionnaire was applied to a sample of (384) teachers. The study concluded that the degree of achievement of training patterns at the specialized institute was high. Moreover, the level of professional development of teachers was also high. The study concluded that there is a statistically significant and strong positive correlation between all the training patterns scale and all the professional development areas scale. The finding of liner regression analysis showed that degree of contribution of training patterns at the Specialized Institute could predict 77.7% of level of the professional development of teachers.